Gross and histomorphological observations on the effect of 2 watt/cm2 therapeutic ultrasound in experimental acute arthritis in the donkeys** - SINGH, K I; SOBTI, V K; ROY, K S; BANSAL, P S (The Indian Journal of Animal Sciences, 2013)
Acute aseptic arthritis was induced in 8 healthy donkeys aged 3-4 years and weighing 80-100 kg. The animals were divided into groups A and B of 4 animals each. Group A served as a control whereas in group B, pulsed ultrasound therapy was applied for 10 min @ 2 watt/cm2 starting from- day-2 to day-8 after induction of arthritis. The joint capsule 01 ultrasound therapy group showed mild joint capsule swelling and mildly haemorrhagic synovial membrane as compared to control group. The articular cartilage of control animals was reddish black, extensively eroded, thin and haemorrhagic. The gross appearance of articular cartilage of the treatment group was more near normal. Microscopically, joint capsule showed complete sloughing of the intima layer and subintimal layer showed severe inflammatory reaction qr even complete necrosis of the fibrous capsule and synovial membrane in the untreated animals. In the animals given ultrasound therapy, the joint capsule was near normal. Synovial membrane of untreated animals showed less of AB material and was more PAS-positive ABIP AS reaction was comparable to normal in treated animals. Calcium deposition was not detectable in the joint capsule of the treatment group. Degeneration ofthe articular cartilage was observed microscopically in control group animals. While the articular cartilage of the, ultrasound treated animals was comparable to normal cartilage. The ABIP AS reaction of articular cartilage in ultrasound treated group was comparable to normal.